Inflammatory pathway interactions and cancer multidrug resistance regulation - Mirzaei, Seyed Abbas; Dinmohammadi, Farideh; Alizadeh, Akram; Elahian, Fatemeh (Life sciences (1973), 2019)
Multidrug resistances against chemotherapeutics are among the major challenges related to cancer treatment. Recent studies have demonstrated that different conditions may tune the expression and activity of MDR transporters. For instance, inflammation occurs through a complex cytological process and chemical reactions in the most tumor microenvironment; it can play a critical role in cancer development and is capable of altering the expression and function of MDR transporters. Cytokines, interleukins, and prostaglandins are potent inflammatory mediators that can modulate the expression of MDRs at transcriptional and post-transcriptional levels in the most human cancer cells and tissues and potentially contribute to balance bioavailability of chemotherapeutic agents. Since cancer cases are usually accompanied by inflammatory responses, glucocorticoids and NSAIDs are the primary useful combination chemotherapies in a variety of cancer treatment protocols. In addition to the anti-inflammatory activities of these agents, they exert diverse modulatory effects on MDR-mediated drug resistance via specific mechanisms. Several factors, including cell and MDR-protein types, pharmacokinetics, and pharmacogenetics, mainly influence the regulatory mechanisms. Uncovering the networks between inflammation and multidrug resistance will be clinically helpful in the treatment of malignant cancers and decreasing the cancer mortality rates.